2020
DOI: 10.1155/2020/9785932
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Origanum majorana Methanolic L and Carvacrol on Ischemia/Reperfusion‐Induced Kidney Injury in Male Rats

Abstract: Background. The most important cause of acute renal failure in normal kidneys is ischemia-reperfusion (I/R) injury. The aim of the current study was to investigate the protective effects of Origanum majorana (OM) methanolic extract, carvacrol, and vitamin E on I/R-induced kidney injury in male rats. Material and Method. Thirty Wistar male rats were randomly allocated into 5 groups; sham, I/R, I/R + OM (300 mg/kg), I/R + carvacrol (75 mg/kg), and I/R + vitamin E (100 mg/kg). Renal function markers, oxidant-anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Our results indicated that plasma PCO, as an early index of protein oxidation, markedly elevated in the I/R group in contrast to SC rats, while SP extract (500 mg/kg) significantly reduced it. In agreement with previous studies [ 11 , 35 ], protein oxidation happens in I/R-induced renal damage. Kang et al (2006) observed that ROSs play a vital role in the pathogenesis of I/R damage [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicated that plasma PCO, as an early index of protein oxidation, markedly elevated in the I/R group in contrast to SC rats, while SP extract (500 mg/kg) significantly reduced it. In agreement with previous studies [ 11 , 35 ], protein oxidation happens in I/R-induced renal damage. Kang et al (2006) observed that ROSs play a vital role in the pathogenesis of I/R damage [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, the protective impact of Malva sylvestris L. [ 10 ], Origanum majorana L. [ 11 ], and Salvia miltiorrhiza [ 12 ] have been explored on the I/R-induced damage. Stachys pilifera Benth ( SP ) is one of genera in the family of Lamiaceae, and the genus Stachys is distributed in the tropical and subtropical regions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The harmful effects of ROS can be explained by several mechanisms; they may produce cellular injury including peroxidation of membrane lipids, protein denaturation, and DNA damage [ 45 47 ]. The most sensitive compounds against oxidative stress are lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors can affect cell senescence and the progression of age-related diseases ( Figure 1 ). Oxidative stress is one of the key factors involved in cell damage or injury [ 5 , 6 ]. Endogenous or exogenous agents could induce tissue or organ damage via oxidative stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%